Depression among Adults with Diabetes in Fasa Diabetes Registry System: Risk Factors and Relationship to Blood Sugar Control - Farzaneh Modaresi; Amir Ansari; Babak Pezeshki; Zahra Parou; Aliasghar Karimi; Mahboubeh Eslamzadeh; Fatemeh Ahrari (Fasa University of Medical Sciences, 2022)
Background & Objective: Diabetes Mellitus is a chronic disorder that affects patients physically and mentally. It is a co-existing disorder that can impact disease management adversely and trigger diabetes-related complications. However, it seems that the role of factors associated with depression are underestimated by both patients and physicians. We examined the associations between depression and blood sugar control and the role of associated factors such as demographic features, Glycated hemoglobin(HbA1c), Fasting Blood Sugar, lifestyle and diabetes-related complications on depression in adults with diabetes mellitus. Materials & Methods: We conducted a cross-sectional study among 219 adults diagnosed with diabetes. Participants completed a questionnaire measuring depressive symptoms and demographic backgrounds. Laboratory values and data from physical examination were also collected. Results: The prevalence of depression was 12.3% in our population. The mean level of HbA1c and FBS was also higher among depressed patients. however, it was not significantly different among patients with and without depression. There was no statistically significant correlation between the Beck Depression Scale mean scores and the mean of FBS, HbA1c and BMI (p<0.01). Conclusion: Our findings reveal that depression rate among diabetes patients is considerable. In fact, mental status should be noticed as well as pathological status in clinical practice.